Role and potential therapeutic use of antibodies against herpetic infections. (June 2017) - Clementi, N.; Cappelletti, F.; Criscuolo, E.; Castelli, M.; Mancini, N.; Burioni, R.; Clementi, M.
Abstract: Background: The cellular adaptive response directed against herpesviruses is widely described in the scientific literature as a pivotal component of the immune system able to control virus replication. The role of humoral immunity remains unclear and controversial. Aims: Discussing the role of adaptive immunity in herpesvirus infection control, highlighting the potential role of the humoral branch of immunity through the description of human monoclonal antibodies directed against herpesviruses. Sources: PubMed search for relevant publications related to protective immunity against Herpesviridae. Content: This review describes the role of adaptive immunity directed against Herpesviridae, focusing on the human humoral response naturally elicited during their infections. Given the ever-increasing interest in monoclonal antibodies as novel therapeutics, the contribution of humoral immunity in controlling productive infection, during both primary infection and reactivations, is discussed. Implications: Human monoclonal antibodies directed against the different Herpesviridae species may represent novel molecular probes to further characterize the molecular machinery involved in herpesvirus infection; and allow the development of novel therapeutics and effective vaccine strategies.